Sosialisasi Pencegahan Stunting sebagai Proyek Kemanusiaan KKNT Guna Mendukung Program MBKM di Salama Kelurahan Na’e Kota Bima - Irma Mardian; Kartin Aprianti; Nurkaidah Putri; Nurita Amaliya; Irwati Irwati; Mawardan Mawardan; Afifah Afifah; Muhammad Yusuf (Jurnal Kabar Masyarakat, 2024)
Stunting is a significant nutritional problem in Indonesia, with long-term impacts on children's health and development. This research aims to explore the effectiveness of outreach on stunting prevention through the MBKM Thematic Real Work Lecture (KKNT) humanitarian project implemented in Na'e Village, Salama, Bima City. The method used is a participatory approach, involving local communities in various educational and outreach activities using leaflets regarding the importance of balanced nutrition, good parenting patterns, and access to health services. The results of the activity show an increase in public knowledge about stunting and steps to prevent it. This project not only supports the Independent Learning-Free Campus Program (MBKM) but also strengthens collaboration between students, the community and the local government. The conclusion from this activity is the need for continued education programs to ensure positive behavioral changes in preventing stunting in the area.